Sample preparation combined with electroanalysis to improve simultaneous determination of antibiotics in animal derived food samples - da Silva, Wesley Pereira; de Oliveira, Luiz Henrique; Santos, André Luiz dos; Ferreira, Valdir Souza; Trindade, Magno Aparecido Gonçalves [UNESP] (My University, 2018)
A procedure based on liquid–liquid extraction (LLE) and phase separation using magnetically stirred salt-induced high-temperature liquid-liquid extraction (PS-MSSI-HT-LLE) was developed to extract and pre-concentrate ciprofloxacin (CIPRO) and enrofloxacin (ENRO) from animal food samples before electroanalysis. Firstly, simple LLE was used to extract the fluoroquinolones (FQs) from animal food samples, in which dilution was performed to reduce interference effects to below a tolerable threshold. Then, adapted PS-MSSI-HT-LLE protocols allowed re-extraction and further pre-concentration of target analytes in the diluted acid samples for simultaneous electrochemical quantification at low concentration levels. To improve the peak separation, in simultaneous detection, a baseline-corrected second-order derivative approach was processed. These approaches allowed quantification of target FQs from animal food samples spiked at levels of 0.80 to 2.00 µmol L−1 in chicken meat, with recovery values always higher than 80.5%, as well as in milk samples spiked at 4.00 µmol L−1, with recovery values close to 70.0%.
Keywords: Biological sample preparation; Complex feedstuff samples; Electroanalysis; Residual veterinary drugs